2009
DOI: 10.1111/j.1472-765x.2008.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of food raw materials for the presence of Shiga toxin-producingEscherichia coliO91:H21

Abstract: Aims:  To provide information on the prevalence and detection, in foods, of Shiga toxin‐producing Escherichia coli (STEC) O91:H21. Methods and Results:  Seven hundred fifteen minced beef meats and 205 raw milk samples were analysed by stx‐specific PCR‐ELISA. Samples positive for stx were subsequently tested for the presence of wzy‐O91, fliC‐H21 and the adhesin‐encoding gene saa. For minced meat, 16 (2·2%) and 11 (1·5%) samples were found positive for (stx, wzy‐O91, fliC‐H21) and (stx, wzy‐O91, fliC‐H21, saa) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…However, some studies tested for some of these genes in a few O91 strains. The results that we obtained were mostly consistent with data obtained for two O91:H21 strains isolated from minced meat and raw milk in France (19), four O91:H21 strains isolated from human and bovine sources in Argentina (20), an O91:H21 strain isolated from cattle feces-polluted wastewater in Spain (25), and clinical O91 strains isolated in the European Union (27). From these genotypic studies, we can surmise that the STEC O91 serogroup strains do not have many of the genes that are common in other STEC strains and even differed in the prevalence of genes that are common in other LEE-negative STEC strains, such as serotype O113:H21 strains.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, some studies tested for some of these genes in a few O91 strains. The results that we obtained were mostly consistent with data obtained for two O91:H21 strains isolated from minced meat and raw milk in France (19), four O91:H21 strains isolated from human and bovine sources in Argentina (20), an O91:H21 strain isolated from cattle feces-polluted wastewater in Spain (25), and clinical O91 strains isolated in the European Union (27). From these genotypic studies, we can surmise that the STEC O91 serogroup strains do not have many of the genes that are common in other STEC strains and even differed in the prevalence of genes that are common in other LEE-negative STEC strains, such as serotype O113:H21 strains.…”
Section: Discussionsupporting
confidence: 91%
“…Surveys of nonclinical sources have shown that STEC serogroup O91 strains are also present in foods. These strains have been isolated from raw milk and cheeses in France (17) and Switzerland (18), from minced beef in France (19), and from cattle feces in Argentina (20), and they are the second most common STEC serogroup found in various types of meats and dairy products in Germany (16). In the United States, STEC O91 strains have been isolated from ground beef (21), from the production environments of other food animals, and also from fresh produce (22).…”
mentioning
confidence: 99%
“…Based on epidemiological data, serotype 026, 045, 0103, 0111, 0121, 0145, and 091 STEC strains are responsible for causing most of the reported human cases both worldwide and in the United States (4,5,13,22,23). Strains of E. coli 0157:H7 have been recognized as a foodborne pathogen since the early 1980s (31) and deemed an adulterant in raw ground beef and nonintact beef since 1993 and 1999, respectively (36,37).…”
mentioning
confidence: 99%
“…As rapid diagnosis in the medical field can affect the life and death of the public, the papers below are amongst some of the recent studies reported within the last 5 years on the detection of various diseases and pathogens in the medical diagnosis: identification of cancer cells [1517]; detection of the presence of Hepatitis A, B, C, and E types [14, 1821]; species detection and identification of dermatophyte species [22]; invasive fungal infections in immunocompromised patients [23–25]; detection of poliovirus, enterovirus, and norovirus [26, 27]; and determination of blood group antigens for hemolytic disease of the newborn cases and polytransfused patients [28]. …”
Section: Applications Of Pcr-elisamentioning
confidence: 99%
“…There are also a number of publications using PCR-ELISA in the food industry such as the detection of harmful food-borne pathogens such as Campylobacter sp., Salmonella [6, 2932], Listeria monocytogenes [33, 34], Escherichia coli [26, 35], Brucella melitensis [36], and Vibrio parahaemolyticus [2]. Not limiting the use of the method in the medical and food industries, the study of PCR-ELISA extends even to the veterinary industry.…”
Section: Applications Of Pcr-elisamentioning
confidence: 99%